Compostos clonais como estratégia para mitigar a interação dos clones x ambientes na cultura do eucalipto - Oliveira, Ana Flávia Cunha Fernandes de (2020)
One of the biggest challenges for breeders in large companies, especially those that work with perennial plants, is to identify clones to be recommended, aiming at future commercial plantations and having information from the past, whose environmental conditions are unpredictable. In this condition, breeders seek to study strategies that can mitigate the effects of interaction between clones x environments (GA) at the time of their recommendation for forest exploitation. Given the above, the objective of this work was to study the interaction using compounds in relation to their respective monoclones; to verify if the compound formed from experiments with monoclones (MC) or Single Tree Plot (STP or clonal composites -CC) has different behavior in relation to the interaction; and to verify whether the possibility of determining the ideal number of clones to constitute the compound in the context of mitigating the interaction. Data from 60 clones provided by Suzano S/A were used. The experiments were conducted in six environments involving four states in Brazil. In each environment, the clones were evaluated simultaneously and continuously, in the designs of Single Tree Plot, with 30 replications, and DBC (MC plots with four rows of seven plants, and the ten central plants were evaluated, with three replications). The IMA data (m³.ha-¹.year-¹) in monoclone and in composites, at the age of three, were subjected to analysis of variance by environment and, subsequently, in joint analysis. Two research strategies were used. The first, from the clones with the best performance in MC or CC. The second by simulation, taking the clones entirely at random. Some methodologies were used to assess adaptability, stability, as well as recommendation risk estimates. It was found that the way to identify the clones to constitute the CC does not depend on whether they come from STP or MC experiments; the use of clonal compound proved to be more efficient than that of monoclones to mitigate the GA interaction. In many situations, the contribution of the clonal composites to the interaction was significant. However, associated with high productivity, which indicates that clonal compounds took better advantage of differences in environmental stimuli than most monoclones; the risk estimates for recommending clonal compounds were in most cases lower than for different monoclones; and the clonal composites with ten clones proved to be very effective in mitigating the interaction.